Superradiance of charged black holes in Einstein-Gauss-Bonnet gravity - Fierro, Octavio (2018)
In this paper we show that electrically charged black holes in Einstein-Gauss-Bonnet gravity suffer from a superradiant instability. It is triggered by a charged scalar field that fulfils Dirichlet boundary conditions at a mirror located outside the horizon. As in general relativity, the unstable modes exist provided that the mirror is located beyond a critical radius, making the instability a long wavelength one. We explore the effects of the Gauss-Bonnet corrections on the critical radius and find evidence that the critical radius decreases as the Gauss-Bonnet coupling α increases. Due to the, up to date, lack of an analytic rotating solution for Einstein-Gauss-Bonnet theory, this is the first example of a superradiant instability in the presence of higher curvature terms in the action.